2020
DOI: 10.3390/nu12030794
|View full text |Cite
|
Sign up to set email alerts
|

Phycobiliproteins from Arthrospira Platensis (Spirulina): A New Source of Peptides with Dipeptidyl Peptidase-IV Inhibitory Activity

Abstract: Arthrospira platensis (spirulina) is a cyanobacterium, which contains mainly two phycobiliproteins (PBP), i.e., C-phycocyanin (C-PC) and allophycocyanin (APC). In this study, PBP were hydrolyzed using trypsin, and the composition of the hydrolysate was characterized by HPLC-ESI-MS/MS. Furthermore, the potential anti-diabetic activity was assessed by using either biochemical or cellular techniques. Findings suggest that PBP peptides inhibit DPP-IV activity in vitro with a dose-response trend and an IC 50 value … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 31 publications
2
27
0
Order By: Relevance
“…In addition, SP reduces the DPP-IV activity by 64.6% in vitro and 31.7% on Caco-2 cells, while ST reduces it by 74.2% in vitro and 39.8% on Caco-2 cells (at the dose of 5 mg/mL) [ 14 ]. In addition, the tryptic digest of phycobiliprotein purified from spirulina inhibits the DPP-IV activity by 95.8% in vitro, whereas it inhibits it by 44% in situ at 5 mg/mL [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, SP reduces the DPP-IV activity by 64.6% in vitro and 31.7% on Caco-2 cells, while ST reduces it by 74.2% in vitro and 39.8% on Caco-2 cells (at the dose of 5 mg/mL) [ 14 ]. In addition, the tryptic digest of phycobiliprotein purified from spirulina inhibits the DPP-IV activity by 95.8% in vitro, whereas it inhibits it by 44% in situ at 5 mg/mL [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…[4] Due to an increasing concern in animal welfare and the rising environmental awareness, [5] the consumption of vegetable products is becoming a common trend. In this way, a growing body of evidence has underlined several biological actions such as immune, [6,7] antioxidant [6,8] and metabolic [9][10][11] effects of different vegetable protein hydrolysates by in vitro or pre-clinical approaches. We have previously shown that Lupinus angustifolius protein hydrolysates (LPHs), generated by hydrolyzation with the commonly used food-grade endopeptidase Alcalase 2.4 L, inhibit the enzymatic activity inflammatory enzymes phospholipase A2, cyclooxygenase 2, thrombin, and transglutaminase in a cell-free system.…”
Section: Introductionmentioning
confidence: 99%
“…Glucagon-like peptide-1 (GLP-1) is synthesized in the L-cells of the small intestine as a glucagon-containing precursor peptide, and is involved in the inhibition of glucagon secretion and the promotion of insulin secretion in the pancreas [ 28 ]. The N-terminal dipeptides of the GLP-1 are cleaved by DPP-IV (EC 3.4.14.5), and the cleaved GLP-1 acts as an antagonist to the above physiological effects [ 29 ]. Therefore, the inhibition of DPP-IV is an effective way to prevent and treat diabetes.…”
Section: Resultsmentioning
confidence: 99%